Analysis of The Impact of Transportation Infrastructure Investment on Regional Economic Growth of Lombok Barat Regency - Rini Sri Astutik; Muhammad Alwi; Masrun, Masrun (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
The availability of good transportation infrastructure is very important in increasing regional affordability and accelerating regional economic progress and can increase GRDP in a region. The purpose of this study is to analyze the impact of transportation infrastructure investment, including road infrastructure and port infrastructure on regional economic growth in West Lombok Regency. The research method used is quantitative method. The results of this study indicate that road infrastructure (road length) has a probability value of 0.0343 <0.05 with a coefficient value of -15.39090. Thus it is concluded that road infrastructure (road length) partially has a negative and significant impact on regional economic growth in West Lombok Regency. Then, the port infrastructure variable (ship visits), with a probability value of 0.2356> (0.05) and a coefficient value of -1.868806 so it is concluded that partially port infrastructure (ship visits) has a negative and insignificant impact on regional economic growth in West Lombok Regency. In the overall context (simultaneously), when road length and ship visits are analyzed together, both simultaneously have no significant impact on the regional economic growth of West Lombok Regency, with a probability number of 0.078487 > (0.05).